Dendrite‐Free Sodium Metal Anodes Enabled by a Sodium Benzenedithiolate‐Rich Protection Layer. (19th February 2020) - Zhu, Ming; Wang, Guanyao; Liu, Xing; Guo, Bingkun; Xu, Gang; Huang, Zhongyi; Wu, Minghong; Liu, Hua‐Kun; Dou, Shi‐Xue; Wu, Chao
Abstract: Sodium metal is an ideal anode material for metal rechargeable batteries, owing to its high theoretical capacity (1166 mAh g −1 ), low cost, and earth‐abundance. However, the dendritic growth upon Na plating, stemming from unstable solid electrolyte interphase (SEI) film, is a major and most notable problem. Here, a sodium benzenedithiolate (PhS2 Na2 )‐rich protection layer is synthesized in situ on sodium by a facile method that effectively prevents dendrite growth in the carbonate electrolyte, leading to stabilized sodium metal electrodeposition for 400 cycles (800 h) of repeated plating/stripping at a current density of 1 mA cm −2 . The organic salt, PhS2 Na2, is found to be a critical component in the protection layer. This finding opens up a new and promising avenue, based on organic sodium slats, to stabilize sodium metals with a protection layer. Abstract : Eine Natriumbenzoldithiolat (PhS2 Na2 )‐reiche Schutzschicht, die auf Natrium durch eine einfache Methode in situ synthetisiert wird, verhindert wirksam das Wachstum von Dendriten im Carbonat‐Elektrolyten, was zu einer stabilisierten Natrium‐Metall‐Galvanisierung für 400 Zyklen (800 h) bei wiederholtem Plating/Stripping bei einer Stromdichte von 1 mA cm −2 führt.